PENINGKATAN MUTU KAYU JATI (Tectona grandis) HASIL PENJARANGAN ASAL KABUPATEN CIANJUR - Gunawan Pasaribu; Lolyta Sisilia (Universitas Tanjungpura, 2012)
Teakwood is one of the favourite wood due to its strength, durable and beauty. The quality of teakwood was influenced by plantation site, season and geographic. This study attempts to expose some characteristic of teakwood which is produced from thinning plantation with 1 and 2 hours heat treatments at 170oC also densification 17% and 25% at the same temperature. The result shows that both heat and densification treatments increase the hardness value of teakwood surface. The higroscopisity of teakwood is also increased after heat treatment. On the contrary, the treatment has not influence to the density of teakwood. The colour of teakwood is darker after 1 hour heat treatment. The anatomy character of teakwood is appear being flat due to the pressing process. Key words: Teakwood, spacing plantation, heat treatment, densification